O58: THE IMPACT OF RADIOTHERAPY ON PATIENT-REPORTED OUTCOMES OF IMMEDIATE IMPLANT-BASED BREAST RECONSTRUCTION: RESULTS OF A PROSPECTIVE MULTICENTRE COHORT STUDY. (27th April 2021) - Sewart, E; Turner, N; Conroy, EJ; Cutress, R; Skillman, J; Whisker, L; Thrush, S; Barnes, N; Holcombe, C; Potter, S
Abstract: Introduction: Post-mastectomy radiotherapy (PMRT) is increasing given to improve breast cancer outcomes but can increase complication rates following implant-based breast reconstruction (IBBR). Little, however, is known about the impact of PMRT on patient-reported outcomes (PROs) of IBBR, especially in the context of mesh-assisted techniques. Method: 2108 consecutive women undergoing IBBR at 81 UK centres were prospectively recruited between 2014 and 2016. Demographic, operative, oncological and 3-month complication data were collected, and patients who consented received post-operative questionnaires. An 18-month questionnaire assessed PROs using the validated BREAST-Q. The effect of IBBR on PROs was investigated using mixed-effects regression models adjusted for clinically relevant confounders and including a random effect to account for potential clustering by centre. Result: 1693 iBRA participants underwent mastectomy for malignancy, of whom 1187 (70%) consented to receive the 18-month questionnaire and 732 (43%) completed it. Patients undergoing PMRT (n=214) reported significantly worse scores across 3 BREAST-Q domains: satisfaction with breasts (-6.27 points, p=0.008, 95% confidence interval (CI)[-10.91, -1.63]), satisfaction with outcome (-7.53 points, p=0.002, CI[-12.20, -2.85]) and physical well-being (-6.55 points, p<0.001, CI[-9.43, -3.67]). Overall satisfaction was worse in the PMRT group (OR 0.497, p=0.002, CI[0.32, 0.77]). Use of biological mesh did not ameliorate the impact of PMRT on patient satisfaction (interaction term p-values [0.173 - 0.826]). Conclusion: PMRT adversely affects PROs of IBBR. This should be discussed with patients considering IBBR, especially if PMRT is anticipated or indications are borderline, to enable informed decisions regarding oncological and reconstructive options. Abbrev: PMRT: post-mastectomy radiotherapy, PRO: patient-reported outcome Take-home message: This multicentre, prospective cohort study of 732 patients undergoing implant-based breast reconstruction demonstrates worse 18-month patient-reported outcomes in women who received post-mastectomy radiotherapy than those who did not. These data should be discussed with patients to help them make informed decisions about reconstructive surgery.